The Drosophila homolog of human AF10/AF17 leukemia fusion genes (Dalf) encodes a zinc finger/leucine zipper nuclear protein required in the nervous system for maintaining EVE expression and normal growth. - Bahri, S.M.; Chia, W.; Yang, X. (Mechanisms of Development, 2001)
Sibling neurons in the embryonic central nervous system (CNS) of Drosophila can adopt distinct states as judged by gene expression and axon projection. In the NB4-2 lineage, two even-skipped (eve)-expressing sibling neuronal cells, RP2 and RP2sib, are formed in each hemineuromere. Throughout embryogenesis, only RP2, but not RP2sib, maintains eve expression. In this report, we describe a P-element induced mutation that alters the expression pattern of EVE in RP2 motoneurons in the Drosophila embryonic CNS. The mutation was mapped to a Drosophila homolog of human AF10/AF17 leukemia fusion genes (alf), and therefore named Dalf. Like its human counterparts, Dalf encodes a zinc finger/leucine zipper nuclear protein that is widely expressed in embryonic and larval tissues including neurons and glia. In Dalf mutant embryos, the RP2 motoneuron no longer maintains EVE expression. The effect of the Dalf mutation on EVE expression is RP2-specific and does not affect other characteristics of the RP2 motoneuron. In addition to the embryonic phenotype, Dalf mutant larvae are retarded in their growth and this defect can be rescued by the ectopic expression of a Dalf transgene under the control of a neuronal GAL4 driver. This indicates a requirement for Dalf function in the nervous system for maintaining gene expression and the facilitation of normal growth.